MECHANISMS FOR PROTECTING THE LABOR RIGHTS OF EMPLOYEES IN THE SYSTEM OF SOCIAL PARTNERSHIP (Revista Inclusiones, 2020)
The article considers the impact of mechanisms for protecting the labor rights of employees on their protection level in the system of social partnership. The authors' methodology is based on a system of methods, with the Likert scale and an in-depth focused interview used as the main ones. The authors have analyzed the knowledge of labor law as a mechanism for protecting the employee's rights, the degree of trust in protection institutes in case of violated labor rights and the degree of willingness to participate in protests and the joint actions of trade unions.